Effectiveness of vitamin D supplementation in the early gestational period on lactational mastitis development: A new framework in the risk sssessment (Annals of Medical Research, 2022)
Background: Vitamin D (VD) deficiency is known to play a role in many infectious diseases with its immunomodulator effect. We aimed to determine whether optimal VD replacement for women who are deficient in VD, starting from early pregnancy was significantly protective against lactational mastitis (LM).Methods: This retrospective study was conducted with 132 lactating women applied to general surgery outpatient clinic of a university hospital between February 2021 and May 2021 and divided into two groups as those who used VD supplementation (Group 2) starting from the early gestational period and those who did not receive this supplementation (Group 1). The primary outcome was the effect of treatment of maternal VD deficiency or insufficiency on LM, an inflammatory condition of breast during lactational period ranging from a mild to severe forms. The demographic, birth and breastfeeding-related data including nipple crack and occurrence of LM and laboratory parameters concerning VD metabolism were analyzed and compared between the groups.Results: The rates of nipple crack, mastitis attack, recurrent mastitis attack and abscess drainage were statistically significantly higher in Group 1 (p
Keywords: Lactational mastitis; prevention; vitamin D; vitamin D supplementation; pregnancy; lactation